2017
DOI: 10.1111/hel.12425
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and clinical evidence uncovers the enterohepatic species Helicobacter valdiviensis as a potential human intestinal pathogen

Abstract: Horizontal gene transfer has contributed to shape the gene repertory of H. valdiviensis, which codes for virulence factors conserved in other pathogens that are well-known human pathogens. Additionally, the detection of H. valdiviensisDNA in diarrheic patients supports its role as a potential emergent intestinal pathogen. Further, sampling efforts are needed to uncover the clinical relevance of this species, which should be accomplished by the isolation of H. valdiviensis from ill humans and the obtention of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Although EHH are frequently detected in clinical samples by PCR (Fox, ; Mateos‐Muñoz et al, ; Fresia et al, ), only occasionally they are isolated using medium and atmospheric conditions designed for Campylobacter spp. According to the Bergey’s Manual, there is no ideal method for the isolation of EHH and the recovery of these species is often optimized by the simultaneous use of selective and nonselective procedures (On et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EHH are frequently detected in clinical samples by PCR (Fox, ; Mateos‐Muñoz et al, ; Fresia et al, ), only occasionally they are isolated using medium and atmospheric conditions designed for Campylobacter spp. According to the Bergey’s Manual, there is no ideal method for the isolation of EHH and the recovery of these species is often optimized by the simultaneous use of selective and nonselective procedures (On et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Enterohepatic species of the genus Helicobacter (EHH) have become increasingly important as emerging pathogens (Collado et al, 2014;Fresia et al, 2017) due to their association with acute gastroenteritis, inflammatory bowel disease (Crohn's disease and ulcerative colitis) and liver, gallbladder and bile ducts diseases (Man et al, 2008;Martel et al, 2009;Bascuñana et al, 2011;Thomson et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Another genome sequencing study, coming from Chile and Uruguay, compared the genome of Helicobacter valdiviensis to other Helicobacter species. The study showed that H. valdiviensis belongs to a monophyletic clade formed by Helicobacter canadensis , Helicobacter pullorum , Helicobacter winghamensis , Helicobacter rodentium , and Helicobacter apodemus . Additional PCR analyses revealed the presence of H. valdiviensis in some of stools samples of patients with acute diarrhea suggesting a potential role as an intestinal pathogen.…”
Section: Taxonomy Prevalence and Diagnosis Of Non‐helicobacter Pylomentioning
confidence: 88%
“…The study showed that H. valdiviensis belongs to a monophyletic clade formed by Helicobacter canadensis, Helicobacter pullorum, Helicobacter winghamensis, Helicobacter rodentium, and Helicobacter apodemus. 3 Additional PCR analyses revealed the presence of H. valdiviensis in some of stools samples of patients with acute diarrhea suggesting a potential role as an intestinal pathogen. Another interesting study looked at the microbiome composition in coelomic fluid of marine invertebrates.…”
Section: Ta Xonomy Pre Valen Ce and D Iag Nos Is Of Non -Helicobmentioning
confidence: 98%
“…For example, the H. pylori cag pathogenicity island is intimately associated with increased potential to cause more severe pathology, including cancer and gastric ulcers (25). There were five fragments with anomalous GC content in the H. himalayensis genome, and the predicted genome These helicobacters with the term "enterohepatic helicobacters (EHH)" colonize the intestinal mucosa or the liver, and are associated with chronic liver or intestinal inflammation (27). Recently, many cases of EHH infection in humans were reported,…”
Section: Discussionmentioning
confidence: 99%